Dirac and Majorana field operators with self/antiself charge‐conjugate states. Issue 1 (28th March 2019) - Dvoeglazov, V. V.
Abstract : We discuss relations between Dirac and Majorana‐like field operators with self/antiself charge‐conjugate states. The connections with recent models of several authors were found.